Overfeeding increases postprandial endotoxemia in men: Inflammatory outcome may depend on LPS transporters LBP and sCD14. Issue 7 (31st March 2014) - Laugerette, Fabienne; Alligier, Maud; Bastard, Jean‐Philippe; Drai, Jocelyne; Chanséaume, Emilie; Lambert‐Porcheron, Stéphanie; Laville, Martine; Morio, Béatrice; Vidal, Hubert; Michalski, Marie‐Caroline
<x xml:space="preserve">Abstract</x> Scope Low‐grade inflammation is a recognized hallmark of obesity. Endotoxins absorbed after high‐fat meals have recently been implicated. Plasma lipopolysaccharides binding protein (LBP) and soluble cluster of differentiation 14 (sCD14) have also been suggested as clinical markers of endotoxemia. In mice, the ratio LBP/sCD14 has been associated with high fat diet induced inflammation. We tested the hypothesis that healthy subjects develop inflammation differently during weight gain according to changes of LBP/sCD14 ratio. Methods and results Eighteen healthy men were overfed during 8 wk (+760 kcal/day). Endotoxemia, sCD14, LBP, and IL‐6 were measured before and after overfeeding (OF) at fasting (n = 18) and postprandially (subcohort, n = 8). OF did not modify fasting IL‐6 but increased the LBP/sCD14 ratio (P = 0.017). Subjects were categorized into tertiles for LBP/sCD14 ratio variation. Subjects in the highest tertile (+90% LBP/sCD14) increased plasma IL‐6 (+26%) versus the lowest tertile due to a decrease of sCD14 associated with high LBP. The postprandial accumulation of endotoxins increased after OF (+160%). However, only four responding subjects presented increased postprandial IL‐6 accumulation. Conclusion OF increases postprandial endotoxemia but the inflammatory outcome may be modulated by endotoxin handling in plasma. This study supports a new concept whereby inflammation setup during the initial phase of weight gain is linked to the relative variations of LBP and sCD14.